Physical Insights on the Lattice Softening Driven Mid‐Temperature Range Thermoelectrics of Ti/Zr‐Inserted SnTe—An Outlook Beyond the Horizons of Conventional Phonon Scattering and Excavation of Heikes' Equation for Estimating Carrier Properties. Issue 28 (9th June 2021) - Muchtar, Ahmad Rifqi; Srinivasan, Bhuvanesh; Tonquesse, Sylvain Le; Singh, Saurabh; Soelami, Nugroho; Yuliarto, Brian; Berthebaud, David; Mori, Takao
Abstract: Most of the best known SnTe‐based materials exhibit an attractive thermoelectric figure of merit ( zT ) only at the high‐temperature regime, but their performance at the low‐mid temperature ranges is quite uninspiring, and this discordance necessitates a large temperature gradient (∆ T  ≥ 550 K) to effectuate a reasonable efficiency, η. Here, the transition elements, Ti and Zr, that have not been used in the past are tried as dopants for SnTe and an enhanced device/average zT and/or η are reported with a lower ∆ T  ≈ 400 K and without the requisite for a stupendous peak/maximum zT . This notable performance emanates from—i) improved weighted mobility by optimally balancing between effective mass, carrier concentration, and mobility, ii) coupling of charge carriers with magnetic entropy, and the paramount factor being the iii) weakening of the chemical bonds (lattice softening). The thermal damping caused by lattice softening affects the phonon group velocity and the elastic properties, and the resultant increase in the degree of anharmonicity and the high density of internal strain‐fields, along with the phonon scattering effects, play an active role in tuning the overall thermoelectric performance. This work also excavates/opens up the discussion of applying the Heikes' equation to qualitatively compare the trend of charge carriers for a given thermoelectric material system. Abstract : By strategically weakening the chemical bonds and increasing the anharmonicity (reduction in phonon group velocity and elastic moduli) in Zr/Ti‐Mn inserted SnTe, and by coupling of charge carriers with magnetic entropy and engineering the electronic bands, high thermoelectric efficiency is attained with a much lower temperature gradient (Δ T ) without the requisite for a stupendous peak figure of merit ( zT max ).